Analisis Penurunan Pelanggan Barbershop dengan Penerapan Konsep 4P Marketing Mix - Ahmad Hilmy Fawwazni; Ahmad Ashhabul Mubin; Jiddan Muhiza; Budiharjo, Budiharjo (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study analyzes customer attrition in barbershops through the application of the 4P marketing mix, which includes Product, Price, Place, and Promotion. The research was conducted using a questionnaire distributed to 30 barbershop customers, which aimed to assess their level of satisfaction regarding each element of the marketing mix. The findings revealed that while customers were generally satisfied with the quality of the haircuts and the cleanliness of the tools, there was an important demand for improvement in the quality and variety of additional products offered. The pricing strategy was considered affordable by most customers; however, some expressed dissatisfaction, indicating the need for better communication regarding the value of the services provided. Demographic analysis showed that the majority of respondents were young adults aged 18-25, highlighting a specific target market for barbershops. Overall, this study emphasizes the importance of effectively implementing the marketing mix to improve customer retention and satisfaction in the barbershop industry.